AIAA SPACE 2013 Conference and Exposition 2013
DOI: 10.2514/6.2013-5433
|View full text |Cite
|
Sign up to set email alerts
|

Internal Layout for a Cis-Lunar Habitat

Abstract: The distance between Orlando, FL and Miami, FL is 377 km (234 mi.). This is the approximate orbital altitude of the Russian Salyut and MIR space stations; Skylab and the existing International Space Station (ISS). With the exception of the Apollo missions, virtually all human space flight has occurred within the distance between Orlando and Miami. In other words, very close to the Earth. This is significant because NASA's goal is to explore Beyond low-Earth Orbit (BEO) and is building the Space Launch System (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The overall layout is nearly identical to an 8.4 m diameter habitat module that has been presented in previous papers. 3,4,5 The end domes are open and used for translation between decks and provide access to an airlock at one end and docking ports at each end. Several important findings from this configuration are as follows.…”
Section: B 72 M Diameter Habitat Modulesmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall layout is nearly identical to an 8.4 m diameter habitat module that has been presented in previous papers. 3,4,5 The end domes are open and used for translation between decks and provide access to an airlock at one end and docking ports at each end. Several important findings from this configuration are as follows.…”
Section: B 72 M Diameter Habitat Modulesmentioning
confidence: 99%
“…The 8.4m diameter habitat module uses the same three-deck layout as shown in Figures 10 and 11 for the 7.2 m diameter module and has been shown is several previous papers. 3,4,5 Additional volume is available in all areas proportionately due to the larger diameter. Several important findings from this configuration are as follows:…”
Section: 4 M Diameter Habitat Modulesmentioning
confidence: 99%
“…Vertical or transverse layouts were explored too, where the barrel section is turned up in a vertical orientation and the decks stack on top of each other in three or more levels. 8 In general, it was found that the vertical layouts were slightly more massive due to the inefficiency of the layout on each floor-which had to accommodate the circular exterior wall in plan and pass-through at each floor to accommodate vertical circulation. It should be noted, however, that a vertically oriented layout might be appropriate for artificial gravity configurations where a vehicle, like the one shown in Fig.…”
Section: Configuration C-3 Mars Transit Habitatmentioning
confidence: 99%